Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1093/glycob/cwq200
|View full text |Cite
|
Sign up to set email alerts
|

Differences in CD75s- and iso-CD75s-ganglioside content and altered mRNA expression of sialyltransferases ST6GAL1 and ST3GAL6 in human hepatocellular carcinomas and nontumoral liver tissues

Abstract: The sialic acid-specific cytotoxic lectin viscumin and its recombinant equivalent rViscumin specifically bind to CD75s-gangliosides with terminal Neu5Acα6Galβ4GlcNAc sequence. We, therefore, comparatively analyzed the content of CD75s-gangliosides and closely related iso-CD75s-gangliosides (terminated by Neu5Acα3Galβ4GlcNAc sequence) and the gene expression of associated β-galactoside α-2,6-sialyltransferase 1 (ST6GAL1) and β-galactoside α-2,3-sialyltransferase 6 (ST3GAL6), respectively, in 35 hepatocellular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…In colon cancer, ST6Gal.1 over-expression leads also to the expression of an α1,2-fucosylated variant of Sia6LacNAc: the STH2 antigen (Fucα1-2(NeuAcα2-6)Galβ1-4GlcNAcβ1-3Galβ1-4Glc-Cer) (114). In human hepatocarcinomas, only a minority of the patients exhibits increased ST6Gal.1 expression (115), while ST6Gal.1 and α2,6-sialylated glycans show an altered distribution (116,117). In breast cancer, high ST6Gal.1 is associated with poor prognosis markers, such as high grade and absence of progesterone receptor (118).…”
Section: α26-sialylated Lactosamine (Sia6lacnac)mentioning
confidence: 99%
“…In colon cancer, ST6Gal.1 over-expression leads also to the expression of an α1,2-fucosylated variant of Sia6LacNAc: the STH2 antigen (Fucα1-2(NeuAcα2-6)Galβ1-4GlcNAcβ1-3Galβ1-4Glc-Cer) (114). In human hepatocarcinomas, only a minority of the patients exhibits increased ST6Gal.1 expression (115), while ST6Gal.1 and α2,6-sialylated glycans show an altered distribution (116,117). In breast cancer, high ST6Gal.1 is associated with poor prognosis markers, such as high grade and absence of progesterone receptor (118).…”
Section: α26-sialylated Lactosamine (Sia6lacnac)mentioning
confidence: 99%
“…Previous studies with HCC patients have focused on the abnormal expression of glycoproteins (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Souady et al recently reported that CD75s-and iso-CD75s-ganglioside expression in HCC cells is associated with poor histopathological differentiation (19). However, knowledge about neutral GSLs in HCC is lacking.…”
mentioning
confidence: 99%
“…(21)(22)(23) A study has shown that ST3GAL6 expression was significantly reduced in HCC. (24) However, in our previous study, we found that ST3GAL6 was upregulated in MHCC97-H cells relative to MHCC97-L cells. (25) To further investigate the effect of ST3GAL6 in HCC, we measured the ST3GAL6 expression level in HCC cells and tissues relative to non-cancerous cells and tissues.…”
Section: Discussionmentioning
confidence: 62%